Keajaiban Hujan Dalam Prespektif Sains Dan Islam - Anip Dwi Saputro (Universitas Alma Ata, 2015)
Abstract Rotation of the earth’s water cycle is cycles that are amazing and prove the power, the greatness of Alloh the Creator. Because the water supply in the earth as a whole is always fixed and measured in accordance with the necessities of life on earth. Cycle between vapor and rain water purifies itself serves earth where there are trillions of creatures population with all form and types of life and inanimate every time. This cycle also serves to maintain the balance of heat on the surface of the earth and minimize heat in summer. As such, it serves to minimize the difference between the heat of summer and winter. So that life on earth with all form maintained and preserved. Because the total water that evaporates into gas annually layer remains, as well as the total water vapor brought this gas layer, then the total rainwater that feel to earth each year remains same. The difference is only a drop in volume in a place with others places that adjusts the will of Alloh. Average rainfall reaches the earth’s surface is now 85.7 cm3 every year. This volume ranges from zero in the dry desert region and barren until 11.45 meters3 of years in the islands and forest. Keyword: water cycle, summer, volume ranges.